The role of the Code of Canon Law in fulfilling the mission of the Church - DYDUCH, JAN (Prawo Kanoniczne, 2014)
November 27, 2013 marks the 30th anniversary of coming into effect of the current Code of Canon Law. The law is a very useful tool for the Church community. The Church leads Her people to salvation by exercising threefold office of the Church: teaching, sanctifying, and governing. The code in question regulating munera, is at the service of salvation and accomplishes the principle salus animarum suprema lex.